Haid Perspektif Al-Qur’an; Analisis Terhadap Ayat Kesehatan Reproduksi Wanita QS. Al-Baqarah/2: 222-223 - Tangngareng, Tasmin; Rayyn, I Gusti Bagus Agung Perdana; Mahar, Al-Fiana (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2023)
This article describes menstruation that occurs in women as a monthly cycle and also as a form of self-purification and purification of the female reproductive organs. In this article, there are several important topics that will be discussed, namely, an overview of QS. al-Baqarah, a study of verses on menstruation or reproductive health in women, as well as commentators' views on the verses of menstruation or reproductive health in women. Therefore, it is important to discuss the discussion so as not to cause misunderstandings and add insight about menstruation and maintaining reproductive health in women. This discussion is reviewed by conducting library research using an interpretive approach and health sciences. The conclusion is that menstruation is a natural cycle that occurs in every woman as a form of self-purification and cleaning of dirt in the reproductive organs.